An experimental study on discharge characteristics in a pulsed-dc atmospheric pressure CH3OH/Ar plasma jet. (16th August 2016) - Qian, Muyang; Liu, Sanqiu; Yang, Congying; Pei, Xuekai; Lu, Xinpei; Zhang, Jialiang; Wang, Dezhen
Abstract: Recently, C/H/Ar plasma discharges found enormous potential and possibility in carbonaceous compounds conversion and production. In this work, a pulsed-dc CH3 OH/Ar plasma jet generated at atmospheric pressure is investigated by means of optical and electrical diagnosis concerning the variation of its basic parameters, absolute concentration of OH radicals, and plasma temperature with different CH3 OH/Ar volume ratios, in the core region of discharge with needle-to-ring electrode configuration. The voltage–current characteristics are also measured at different CH3 OH/Ar ratios. Laser-induced fluorescence (LIF) results here show that only small amounts of added methanol vapor to argon plasma (about 0.05% CH3 OH/Ar volume ratio) is favorable for the production of OH radicals. The optical emission lines of CH, CN, and C2 radicals have been detected in the CH3 OH/Ar plasma. And, the plasma temperatures increase with successive amount of added methanol vapor to the growth plasma. Moreover, qualitative discussions are presented regarding the mechanisms for methanol dissociation and effect of the CH3 OH component on the Ar plasma discharge at atmospheric pressure.